Financial Ratio Analysis to Assess Financial Performance of the Hotel Industry - Tjeng Gloria Santoso; Supatmi Supatmi (Universitas Pendidikan Ganesha, 2021)
Analysis of financial performance can be implemented to all companies, including to hotel industries. For the last few years, there are many issues that income of hotel industry increases because of the soaring numbers of foreign and domestic tourists in Indonesia. This study aims to analyze financial ratio to assess the financial performance of hotel industry in 2015-2018. Research sample were 12 companies of 35 hotel industries that were listed in Indonesian Stock Exchange in 2015-2018. Analysis tool used in this research were liquidity ratio, profitability ratio, activity ratio, leverage ratio, and operational ratio. Research result showed good ratios; they were liquidity ratio that was indicated by current ratio, profitability ratio that was pointed by net profit margin, return on asset, and return on equity, also paid occupancy percentage on activity ratio. While the not good ratio, which was activity ratio was pointed by total asset turnover, then leverage ratio by equity multiplier, debt to asset ratio, and debt to equity ratio, also operational ratio which was showed through average room rate and food and beverage cost. Research result of hotel performance in 2015-2018 which is based on financial ratio, they are liquidity, activity, profitability, leverage, and operational, describes that hotel performance is fluctuated. Generally seen, a good ratio in this study is the liquidity ratio that is pointed by current ratio, then profitability ratio that are demonstrated by NPM, ROA, and ROE, also paid occupancy percentage in activity ratio.